2009
DOI: 10.1021/cg900105u
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph-Directing Seeding of Entacapone Crystallization in Aqueous/Acetone Solution Using a Self-Assembled Molecular Layer on Au (100)

Abstract: Crystallization of the active pharmaceutical ingredient Entacapone, which exhibits strong polymorphic behavior in aqueous/acetone solutions, is examined with and without the presence of a self-assembled molecular layer of Entacapone (SALE) on an Au (100) surface. SALE characterization by electrochemical and spectroscopic tools confirms the existence of a well-ordered layer structure. These surfaces are found to act as nucleation catalysts providing polymorph-specific templates which enable secondary nucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…The solubility of Entacapone in acetone solution was found to be several orders of magnitude higher than for the mixed aqueous/acetone solution studied previously 6 and close to the ideal predicted (Figure 3), revealing that solute/solute interactions are preferred for both solvents but that solute/solvent interactions in acetone is perhaps a bit stronger in the absence of water. Such wide MSZWs are not that uncommon for organic systems 25,26 .…”
Section: Solubilitysupporting
confidence: 74%
See 2 more Smart Citations
“…The solubility of Entacapone in acetone solution was found to be several orders of magnitude higher than for the mixed aqueous/acetone solution studied previously 6 and close to the ideal predicted (Figure 3), revealing that solute/solute interactions are preferred for both solvents but that solute/solvent interactions in acetone is perhaps a bit stronger in the absence of water. Such wide MSZWs are not that uncommon for organic systems 25,26 .…”
Section: Solubilitysupporting
confidence: 74%
“…Indeed, it is a common and anecdotal observation in industrial crystallization practice that the first crystallisation in a freshly cleaned reactor can be quite different in nature with respect to subsequent crystallisations (see e.g. reference 6 ). This is often related to surface effects, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full Surface-enhanced Raman spectroscopy (SERS) has been recently used for quantitative analysis of the two isomers in solution (30). It has also been demonstrated that the E-isomer crystallizes in six polymorphic forms, named A' (25), D (26), a, b, g and d (27), the first two being the most common in polar solvents (28). Furthermore, form A has been found to be the most stable phase thermodynamically.…”
Section: Resultsmentioning
confidence: 99%
“…Entacapone is clinically used as a therapy for Parkinson's disease (25), which is associated with a lack of dopamine. The solvents were chosen according to the solubility of entacapone and the fact that they were common solvents used in the production process (26)(27)(28).…”
mentioning
confidence: 99%